THE IMPORTANCE OF THE PLACE AND ROLE OF PROFESSIONAL ORGANIZATIONS IN THE PROCESS OF AUDITING ACTIVITY REGULATION IN GEORGIA (International Journal of Innovative Technologies in Economy, 2022)
Regulation of audit activities and quality control of these activities in Georgia gradually developed from the second half of the 90s of the last century and ended with the fact that for this purpose the state created the accounting, reporting and audit supervision service (SARAS) in the Ministry of Finance as a structural unit of the Ministry. Before that, the state could not effectively and strictly control the audit activities and this role was entrusted to the professional organization - the Georgian Federation of Professional Accountants and Auditors (GFPAA), and earlier there was the Council of Audit Activities under the Parliament of Georgia. But this positive event also led to negative events, which, in my specific opinion, I can consider: 1. Strong monopolistic role of the state and weakening of the role of professional organizations; 2. Serious threat of liquidation of small and medium audit firms and oligopolization of audit services in the hands of large audit firms; Real prospective threat of unemployment of auditors employed in small and medium audit firms. The subject of the research of this topic is the role of professional organizations in the process of auditing activity regulation.